Randomized Control Study of the Implementation and Effects of a New Mental Health Promotion Program to Improve Coping Skills in 9 to 11 Year Old Children: Passport: Skills for Life - Mishara, Brian L.; Dufour, Sarah (Frontiers in Psychology, 2020)
Passport: Skills for Life is a universal, primary school mental health promotion program to increase children’s coping skills. A stratified randomized control study with pretest, post-test and 1-year follow-up included 1,492 3rd to 6th grade children, from higher and lower socio-economic levels, randomly assigned by school to receive the program or a control group. Implementation and effects were evaluated by questionnaires and focus groups with children, parents and teachers as well as classroom observations. Program activities were well implemented and greatly appreciated, with perceived improvements in resolving conflicts, communicating feelings and coping. Compared to the controls, participants had increased emotional awareness, sustained 1 year later; conceived of more ways to cope in fictitious situations and reported using more, and more useful strategies, sustained 1 year later. Positive Academic Behaviors increased, but were not sustained the following year. This is a promising program to improve coping and emotional awareness that merits further research on its effects.